Variability, heritability, character association, path analysis and morphological diversity in snake gourd - Khan, A.S.M. Mahbubur Rahman; Eyasmin, Rabeya; Rashid, M. Harunur; Ishtiaque, Sheikh; Chakia, Apurbo Kumar (Agriculture and Natural Resources, 2016)
Genetic variability, heritability and path coefficient analysis were studied in 21 genotypes of snake gourd. The phenotypic coefficient of variations was found slightly higher than the genotypic coefficient of variations for all characters studied, indicating that the apparent variation is not only genetic but also influenced by the growing environment in the expression of the traits. The genotypic coefficient of variation was high for the fruit yield, number of fruits per vine, length of fruit and single fruit weight. High heritability coupled with high-to-moderate genetic advance was estimated for all characters studied. Correlation studies revealed that the fruit yield had a significant, positive correlation with the number of fruits per vine, length of fruit and single fruit weight. Importantly, more than 90% of the genotypic total variation was contributed by the characters included in the path analysis. The highest, direct, positive effect was recorded for the number of fruits per vine. The divergence value for cluster analysis indicated that the genotypes from clusters II and III had the highest inter-cluster distance and were expected to provide high heterosis in hybridization and to show wide variability in genetic architecture. The selection of high yielding genotypes should give emphasis to the number of fruits per vine, length of fruit and single fruit weight.